Voice pathology detection using interlaced derivative pattern on glottal source excitation. (January 2017) - Muhammad, Ghulam; Alsulaiman, Mansour; Ali, Zulfiqar; Mesallam, Tamer A.; Farahat, Mohamed; Malki, Khalid H.; Al-nasheri, Ahmed; Bencherif, Mohamed A.
Highlights: Interlaced derivative pattern (IDP) based system is introduced for voice pathology detection/classification. First-order derivative of glottal source signal is utilized. Single database and cross databases experiments are performed. In cross-database experiments, the accuracies are 88.5% for detection and 90.3% for classification. Abstract: In this paper, we propose a voice pathology detection and classification method using an interlaced derivative pattern (IDP), which involves an n -th order directional derivative, on a spectro-temporal description of a glottal source excitation signal. It is shown previously that directional information is useful to detect pathologies due to its encoding ability along time, frequency, and time-frequency axes. The IDP, being an n -th order derivative, is capable of describing more information than a first order derivative pattern by combining all the directional information into one. In the IDP, first-order derivatives are calculated in four directions, and these derivatives are thresholded with the center value of each directional channel to produce the final IDP. A support vector machine is used as a classification technique. Experiments are conducted using three different databases, which are the Massachusetts Eye and Ear Infirmary database, Saarbrucken Voice Database, and Arabic Voice Pathology Database. Experimental results show that the IDP based features give higher accuracy than that using other related features in all the three databases. The accuracies using cross-databases are also high using the IDP features.